Reseña - Sánchez López, Sandra Beatriz (2014)
Castro Gómez, Santiago; Flórez Malagón, Alberto y Millán de Benavides, Carmen, ed. Pensamiento colombiano del siglo XX. Bogotá: Pontificia Universidad Javeriana, 2007.